Muamalah Fiqih Review on Return of Rest of Purchase with Goods and Return of Residual Purchase as Infak at Surya Ponorogo Supermarket - Rokhy Irma Azizah; Suad Fikriawan; Nafi'ah Nafi'ah; Tantin Puspitarini (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
Usually in society, buying and selling activities are exchanges between money and goods. If there is a balance from the payment, it will be returned in the form of money, but in practice in the community there are refunds (especially in small amounts) in the form of goods such as candy and also in the form of infaq or alms. This study aims to determine the mashlahah review of the return of the remaining purchases with goods and the return of the remaining purchases as infaq. This research is a field research with a qualitative type of case study at Surya Ponorogo supermarket with data collection techniques through observation of transaction activities, interviews regarding the practice of returning the remaining purchases that cannot be cashed. Then drawing conclusions using the inductive method, which begins with revealing phenomena that are specific in nature and drawing conclusions using general or general theories of Islamic law. Based on the results of the study, the practice of returning the remaining purchases that could not be cashed in in a condition where the spare change was completely depleted. When viewed from the side of mashlahah, it does not conflict with Islamic sharia. Because this policy is part of muamalah activities that are made to eliminate difficulties for the sake of getting benefit. The policy of returning the remaining purchases by the Surya Ponorogo supermarket has considered the concept of mashlahah and does not conflict with existing texts.